‘Can You Tell Me What Ethics Means?’: Collaboration, Voice, and Consent in (Inclusive) Research with People with Learning Disabilities - Gareth M. Thomas (International Journal of Disability and Social Justice)
Accounts of doing ‘inclusive research’ – in which people with learning disabilities are considered as major stakeholders in the research agenda – have proliferated in recent years. These largely focus on the process of such pursuits, including project planning, research design, data collection, and disseminating results. Yet, whilst scholars have identified the challenges of doing inclusive research, they rarely sketch out the more messy, and everyday, ethical moments when doing research with people with learning disabilities. Drawing on an ethnography in two settings run for and/or with people with learning disabilities in the UK, I ponder the use of an advisory committee, the notion of ‘voice’, and the consent process, to explore how my experiences complicate the philosophies of, and desire for, inclusivity . I conclude by urging researchers attempting to work inclusively to put their approaches under the microscope, in ways that can support others to fine-tune their practices.